Atividades investigativas como aporte à argumentação em aulas de ciências - Alves, Adriele Ribeiro (2022)
Investigative teaching has become a central didactic approach in Science Education. It is considered to be fundamental for the promotion of scientific literacy, an objective currently defended, both in official curricular documents and by theorists and researchers in this disciplinary field. Inquiry-based teaching involves activities in which students are encouraged to take an active role in problem solving, developing, in this process, the ability to argue based on evidence, having the opportunity to build knowledge in a dialogic relationship with their peers, before the teacher's mediation, as an epistemic authority. Based on these assumptions, we developed a research that aimed to analyze the arguments produced by students of the 6th year of Elementary School, throughout an investigative teaching sequence (SEI) on anuran amphibians, relating such arguments to the structure of the sequence. This is a qualitative approach research, of an interventional nature, and can be characterized, according to Teixeira and Megid-Neto, as a process and product development research. To meet the proposed objective, the SEI, entitled "Knowing the biodiversity of frogs: differences between toads, frogs and treefrogs", was developed in a public school in Heliópolis-Ba, in four meetings, during classes. of Sciences. Due to the pandemic caused by COVID-19, SEI underwent changes and classes took place through videoconferences, using the virtual platform ZOOM. The data recorded in audio and video were transcribed and, together with the written data, subjected to analysis in the light of the Toulmin Argument Pattern (Toulmin'sArgumentPattern - TAP). Inspired by the Investigative Cycle proposed by Pedaste et al., the SEI was subdivided into stages that demanded student engagement in investigative activities and discursive practices, especially argumentation. The results show that the students' reserve in expressing their points of view during the initial moments of SEI gave way to the presentation of arguments, by most students, in which data and guarantees of inference generated consistent conclusions. The perception about the morphological structures of frogs, related to their habitats, as well as their participation in the ecological balance was evident in the discussions. However, the participation of some students in the activities remained low, which compromised the quality of their arguments. The analysis also reveals that the adequacy of the SEI for its online application guaranteed the space for argumentation, but it seems to have affected the fieldwork of the students individually, in its final part, in view of the low return of the proposed activity. Thus, the results of this research also contribute to the reflection on the potential and limitations of investigative teaching sequences developed in remote classes.